Lost fresh horticultural produce and maintenance of quality in supply Chain: Tropical and sub-tropical fruit - Singh, Zora (International Society for Horticultural Science, 2015)
Tropical and subtropical fruit have unique delicious taste and flavour and contribute to human nutrition. Expansion in tropical and subtropical fruit industry and the global trade liberalization impart a great impetus to the expansion of international trade. The export of tropical and subtropical fruit rose from 21.59 million t (9777.41 million US $) in 2000 to 31.15 million t (23696.00 million US $) in 2009 (FAO, 2012). The production and trade is expected to continue to expand further. The fruit are highly perishable, susceptible to chilling injury, diseases and pests. Postharvest losses vary from 10-80%. The consistent supply of high quality fresh and safe fruit to domestic and international consumers is a great challenge for postharvest biologists and technologists. This paper will delve into the international trade, postharvest losses, current status of postharvest research and challenges; ways to minimise undesirable effects of ethylene on fruit ripening, storage and quality; implication of low temperature, modified atmosphere and controlled atmosphere storage, amelioration of chilling injury, management of postharvest diseases and pests and future research; potentials of biotechnology and ‘omics’ in extending storage life and maintaining quality by ensuring food safety; and the research priorities for the development of postharvest technologies leading to eco-friendly, biologically safe and non-chemical approaches for sustainable postharvest management practices in tropical and sub-tropical fruits.